Immunology of the female genital tract - Weissenbacher, Ernst Rainer (Springer Berlin Heidelberg, 2014)
The mucosal immune system in the female reproductive tract has evolved to meet the unique requirements deriving from the need to deal with sexually transmitted bacterial and viral pathogens, allogeneic spermatozoa, and the immunologically distinct fetus. Despite years of immunologic investigation, the mechanisms that regulate this mucosal immune system have received relatively little attention. This is due to the complexities of the immune and endocrine system and also the difficulties of conducting experiments in this field. This book systematically reviews and discusses recent studies and articles on the immunology of female genital tract tissue. The scope is broad, encompassing innate immune responses, adaptive (humoral and cell-mediated) immunity, the immunology of menstruation, the immunology of viral and bacterial infections, the immunology of normal and abnormal pregnancy, and immunological infertility. Throughout, tables and illustrations are judiciously used to facilitate understanding. Immunology of the Female Genital Tract will serve as an invaluable source of up-to-date information for all with an interest in this subject.